The use of NDYAG laser combined with pulsed light in the treatment of rosacea - Valeriu Ardeleanu; Lavinia Alexandra Moroianu; Vlad Denis Constantin; Petrisor Banu; Florin Silviu Groseanu; Ioana Paunica; Ana Maria Dascalu; Alin Laurentiu Tatu (Journal of Mind and Medical Sciences)
Rosacea is a chronic inflammatory skin disease with a complex pathogenesis that mainly affects the central part of the face, with a global incidence of 5.46%. The present study was performed on a group of 68 patients with rosacea 1 and 2 subtypes, patients between 34-63 years old. The treatments were performed using a Cutera Xeo laser, using 2 types of probes: NdYag 1064nm for telangiectasias and LimeLight 520-1100nm for diffuse facial erythema, papules, and pustules, having an 10x30mm window. For patients with diffuse facial erythema, etc., the optimal number of sessions was between 3 and 6 with or without anesthetic cream, using energies between 14-19J / cm. The average recovery time was 5 days. Registered effects included bruises, pustules, burning sensation, transient stinging, and hypopigmentation. For patients with telangiectasia, the optimal number of sessions was two, performed at an average interval of once per month/ monthly.